PM10 oxidative potential at a Central Mediterranean Site: Association with chemical composition and meteorological parameters. (September 2018) - Pietrogrande, Maria Chiara; Perrone, Maria Rita; Manarini, Francesco; Romano, Salvatore; Udisti, Roberto; Becagli, Silvia
Abstract: An extended study on the oxidative potential (OP) of PM10 particles collected from December 2014 to October 2015 at a peninsular site of the Central Mediterranean basin has been performed. PM10 particles have been selected to better account for all different aged/fresh particle types. Two acellular assays, i.e., the dithiothreitol (DTT) and ascorbic acid (AA) methods, were used to measure the OP of PM10 particles chemically speciated by more than 40 species. DTT and AA assays provide close mean values of volume normalized OPV responses, with similar variability range, i.e., mean OP DTT V = 0.24 ± 0.12 nmol DTT min −1 m −3 and mean OP AA V = 0.29 ± 0.18 nmol AA min −1 m −3 . Also mass normalized OPm responses are similar for both assays, with mean value close to 0.008 nmol min −1 μg −1 . The measured OP DTT V and OP AA V are correlated with several inorganic species, namely ions and metals, and with organic/elemental carbon. The discrimination of the data according seasonality, i.e., Autumn-Winter (AW, October–March) and Spring-Summer (SS, April–September) days, shows a clear seasonal trend of correlation coefficients. In AW, OP DTT V is strongly correlated with nss-K + and nss-Ca 2+, in addition to Ba, Cd, Ce, Cr, Cu, Fe, and Mn (traffic-related metals) and with EC, OC, and POC associated with the traffic exhaust source and/or with the combustion including biomass-burning source. Otherwise, OP DTT V of SS samples is correlated only with NH4 +, Cu, EC, OC, and POC. The OP AA V of AW samples is well correlated with Ba, Ce, Cr, Cu, Fe, Mn, nss-K +, EC, OC, and POC, which are related with traffic and/or combustion emissions. Conversely, in SS, OP AA V is mainly correlated with NH4 +, nss-K +, nss-Mg 2+, nss-Ca 2+, nss-SO4 2−, Cu, Mn, P, Pb, and oxalate, that are species related to secondary aerosols and resuspended soil from vehicular traffic and/or transported Saharan dust. These findings point the importance of both organic components and transition metals to PM oxidative properties, and also suggest that synergistic/antagonistic interactions and cross-correlations between the PM redox-active components are likely responsible for the seasonal variation of the AA and DTT assay response. The inter-correlation among all analysed species has been investigated to explain contrasting results and the negative correlations between OP values and some chemical species. Graphical abstract: Image 1 Highlights: Oxidative potential is assessed for PM10 collected at a Central Mediterranean Site. Two cell-free assays yield similar OPDTT and OPAA responses. Association of OP AA V and OP DTT V with PM chemical components varies with seasons. Metals and primary organic carbon are the main responsible for PM-induced OP. Abstract : Cell-free methods assessed the oxidative potential of particulate matter collected at a Central Mediterranean Site and the results were correlated with PM10 chemical composition.